Reconsidering the Role of Exocrine Pancreatic Insufficiency in Functional Dyspepsia - Akca, Serdar (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Akca S. Reconsidering the role of exocrine pancreatic insufficiency in functional dyspepsia. Turk J Gastroenterol. Published online October 10, 2025. doi:10.5152/tjg.2025.25532.